A test of the Bulut et al. (2016) landmark-free method of quantifying sex differences in frontal bone roundness in a contemporary Czech sample - Čechová, Markéta; Dupej, Ján; Brůžek, Jaroslav; Bejdová, Šárka; Velemínská, Jana (Journal of forensic sciences, 2021)
The skull, along with the pelvic bone, serves an important source of clues as to the sex of human skeletal remains. The frontal bone is one of the most significant sexually dimorphic structures employed in anthropological research, especially when studied by methods of virtual anthropology. For this reason, many new methods have been developed, but their utility for other populations remains to be verified. In the present study, we tested one such approach-the landmark-free method of Bulut et al. (2016) for quantifying sexually dimorphic differences in the shape of the frontal bone, developed using a sample of the Turkish population. Our study builds upon this methodology and tests its utility for the Czech population. We evaluated the shape of the male and female frontal bone using 3D morphometrics, comparing virtual models of frontal bones and corresponding software-generated spheres. To do so, we calculated the relative size of the frontal bone area deviating from the fitted sphere by less than 1 mm and used these data to estimate the sex of individuals. Using our sample of the Czech population, the method estimated the sex correctly in 72.8% of individuals. This success rate is about 5% lower than that achieved with the Turkish sample. This method is therefore not very suitable for estimating the sex of Czech individuals, especially considering the significantly greater success rates of other approaches.
Keywords: senioři; 3D imaging methods; senioři nad 80 let; Computer Simulation; Tomography, X-Ray Computed; počítačové zpracování obrazu; sexual dimorphism; počítačová simulace; Česká republika; Middle Aged; mužské pohlaví; Forensic Anthropology; Frontal Bone; Adult; mladý dospělý; virtual morphometrics; Czech Republic; Sex Determination by Skeleton; Support Vector Machine; frontal bone; Aged, 80 and over; Young Adult; určení pohlaví podle kostry; Humans; zobrazování trojrozměrné; sex estimation; čelní kost; soudní antropologie; lidé středního věku; support vector machine; Imaging, Three-Dimensional; Image Processing, Computer-Assisted; dospělí; počítačová rentgenová tomografie; Aged; lidé; Male; forensic anthropology